Segmentation of the Wild Animal Meat Consumer Market in Belém Municipality, Pará State, Brazilian Amazon - Rebello, Fabrício Khoury; Gonçalves, Paula Cristiane Trindade; Souza, Carina Chagas Madeira de; Santos, Marcos Antônio Souza dos; Bezerra, Andréia Santana; Soares, Bruno Cabral; Lopes, Maria Lúcia Bahia; Loureiro, João Paulo Borges de (Journal of Agricultural Studies, 2022)
The growing demand for nutritious protein-rich foods has increased the visibility of the wild animal meat market, and created an alternative replacement for traditional meats. The informality in this product offer is a characteristic feature of this market. It is necessary to certify the existence of a public in this market niche. This segmentation of the wild animal meat consumer market in Belém municipality, Pará state, in the Brazilian Amazon, was carried out to identify consumers’ perceptions of the economic potential of this activity. Data were obtained from a representative sample of consumers in Belém, one of the most representative consumption centers in the Amazon. Market segmentation was performed using two multivariate techniques: factor analysis to simplify the original data matrix, and cluster analysis to identify homogeneous groups according to the highest degree of similarity of objects in relation to the attributes of interest. The survey results showed that factors such as consumption preferences, product availability, education level, income, and family composition are determinants of the consumption of wild animal meat. The study also confirmed the existence of a market for this product in food establishments such as bars and restaurants. The main wild animal meats consumed were tartaruga-da-Amazônia (Podocnemis expansa) (61.67%), alligator (Alligatoridae) (56.67%), paca (Cuniculus paca) (52.50%), deer (Cervidae) (40.83%), armadillo (Dasypodidae) (40.00 %), muçuã (Kinosternon scorpioides) (30.83%), capybara (Hydrochoerus hydrochaeris) (29.58%), tortoise (Chelonoidis) (21.25%), tracajá (Podocnemis unifilis) (19.58%), peccary (Pecari tajacu) (17.08%) and sloth (Folivora) (12.92%). The expansion of this market, requires strategies to strengthen the regular sustainable supply of the product, including public initiative efforts regarding the regulatory framework of the activity and entrepreneurial efforts for the necessary investments in breeding and slaughtering system officers.